Modulation and distribution of extracellular free water and tract deficits in rhesus macaques before and after the initiation of emtricitabine + tenofovir disoproxil fumarate + dotutegravir treatment - Nguchu, Benedictor Alexander; Lu, Yu; Han, Yifei; Wang, Yanming; Liu, Jiaojiao; Li, Hongjun; Shaw, Peter (Frontiers in Immunology, 2025)
IntroductionUnderstanding the specific timing of cART initiation, its effectiveness, and failures, as well as assessing how well the current cART regimens control viral replication and rebound, enhance immune function, and repair or curb early injury in the central nervous system (CNS), is crucial to improving the livelihood of people living with HIV.MethodsHere, we use an animal model to provide controlled environments to understand how the bodies of Chinese-origin rhesus monkeys, both the immune system and CNS, respond to a combination of emtricitabine (EMTBL/FTC), dolutegravir (DTG), and tenofovir disoproxil fumarate (TDF) following the induction of Simian Immunodeficiency Virus (SIV). We injected the rhesus monkeys with a dose of SIVmac239 (i.e., TCID50—a 50-fold half-tissue culture infective dose) through brachial veins and conducted seven follow-ups at baseline, day 10, day 35, day 84, day 168, day 252, and day 336 for MRI imaging and blood/CSF assays of SIV copies and immunity levels.Results and discussionOur experimental data demonstrate that the immune system is compromised as early as 7 days after infection, with a rapid rise of SIV copies in ml and a significant drop of CD4/CD8 ratio below ~1 within the first 14 days of infection. The alterations in the extracellular environments, manifesting as increased free water volume fraction (FW-VF) in MRI data and changes in the diffusivity properties of fiber tissues appearing in FW-corrected FA and FW-corrected MD, occur in parallel with an compromised immune system, suggesting that SIV enters the brain parenchyma in the early days of infection via a weakened brain defense system, causing inflammatory processes affecting the CNS. Our findings demonstrate that our current FTC+TDF+DTG regimen can enhance the immune system, suppress SIV replication, and slow damage to the intra- and extracellular environments. However, it is still ineffective in controlling viral rebound and experiences resistance in some rhesus monkeys, which may lead to further damage to the CNS. Our findings also provide the first SIVmac239-based evidence that extracellular FW-VF may be a more reliable biomarker of abnormal inflammatory processes, thus providing a better understanding of SIV disease progression than previously anticipated.